Systematic review and meta-analysis of occult contralateral nodal metastases in patients with oropharyngeal squamous carcinoma undergoing elective neck dissection. Issue 2 (February 2023) - Malik, Akshat; Hardman, John C.; Devabalan, Yadsan; Nutting, Christopher; Bhide, Shreerang; Harrington, Kevin; Schilling, Clare; Paleri, Vinidh
Abstract: A systematic review and meta-analysis was conducted to evaluate the occult contralateral nodal metastases (OCM) in patients undergoing bilateral neck dissection for surgically treated oropharyngeal squamous cell carcinoma (OPSCC). Following PRISMA guidelines, MEDLINE, Embase and Cochrane Controlled Register of Trials databases were searched for observational and experimental studies until March 2021. Search yielded 175 articles, of which 13 were included. Overall, OCM were seen in 9.8% of patients (95% CI: [5.7, 16.4], 839 patients, 12 studies, I 2 65%). For ipsilateral cN0 necks, the OCM rate was 1.7% (95% CI: [0.1, 22.4], 150 patients, 8 studies, I 2 0%) and for cN + necks the OCM rate was 9.8% (95% CI: [4.4, 20.3], 429 patients, 8 studies, I 2 72%). Occult contralateral nodal metastases are uncommon in OPSCC patients with clinico-radiologically negative ipsilateral necks. Occult rates are higher in the contralateral neck when the ipsilateral neck is clinico-radiologically node positive.